The development of an assault patient questionnaire to allow accident and emergency departments to contribute to Crime and Disorder Act local crime audits. Issue 3 (1st May 2000) - Goodwin, V; Shepherd, J P
Abstract : Objective —To evaluate and refine an assault patient questionnaire to facilitate the contribution of accident and emergency (A&E) departments to Crime and Disorder Act local crime audits. Method —A brief nine item questionnaire was devised in collaboration with the authors of the Home Office British Crime Survey. A prospective sample of 46 consecutive assault patients who attended Cardiff Royal Infirmary A&E department were interviewed by either reception staff or triage nurses. The questionnaire was revised appropriately. Results —The collection of information in A&E departments about the circumstances of violence was straightforward. Questions about motive for violence and about relationships between the injured and their assailants were problematic. Conclusion —The collection of information relevant to Crime and Disorder Act crime audits was possible without extra resource. Receptionists were found to be the most appropriate staff to record information.